Libraries and the information society in Germany : an introduction - Plassmann, Engelbert; Rösch, Hermann; Seefeldt, Jürgen; Umlauf, Konrad, 1952- (Harrassowitz Verlag, 2014)
Libraries and the Information Society in Germany presents, for the first time, the contemporary German library system not from a library insider's view, but rather from a comprehensively societal perspective. The roles and functions of libraries are analyzed and assessed from this vantage point. The authors - both researchers and practitioners - identify historical developments, describe current trends taking into account sociostructural contexts, and outline options for action. The changes that libraries and library science can embrace and have already embraced in part include, in addition to.